THE IMPACT OF EXCESSIVE GADGET USE ON STUDENTS' CONCENTRATION AND DISCIPLINE IN THE EDUCATIONAL PROCESS - Latif, Abdul; Fitri, Nila Lailatul; Fatin, Gina Ilhami (Universitas Negeri Gorontalo, 2025)
The rapid advancement of digital technology has rendered gadgets anintegral component of students' lives. However, the unregulated use ofthese devices may adversely affect the quality of the teaching and learningprocess (PBM). This study seeks to examine the relationship betweengadget usage and students' learning concentration and discipline atMadrasah Aliyah Kabar, East Lombok. Employing a quantitative designwith a survey approach, complemented by classroom observation, theresearch involved a sample of 70 students selected through purposivesampling. Data collection was conducted using a Likert scalequestionnaire and student learning behavior observation sheets. The datawere analyzed utilizing descriptive statistics and Pearson correlationtests. The findings revealed a significant negative correlation betweengadget use, predominantly for non-educational activities such as socialmedia and digital games, and student learning concentration (r = −0.45; p= 0.001) as well as student discipline (r = −0.38; p = 0.032). This impact isevidenced by reduced attention spans, increased distractions fromnotifications, violations of electronic device usage rules in the classroom,and delays in assignment submission. These results suggest that excessivegadget use can diminish the effectiveness of PBM and have implicationsfor student learning outcomes. Consequently, it is necessary to implementpolicies restricting gadget use within the school environment, enhancedigital literacy and time management among students, and integratetechnology judiciously to support productive learning.